2016
DOI: 10.1111/tri.12872
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up after live donor nephrectomy - cross-sectional and longitudinal analysis of a prospective cohort within the era of extended donor eligibility criteria

Abstract: To establish the outcome of live kidney donors 5 years after donation, we investigated the risk for progressive renal function decline and quality of life (QoL). Data on estimated glomerular filtration rate (eGFR), creatinine, hypertension, QoL and survival were assessed in a prospective cohort of 190 donors, who donated between 2008 and 2010. Data were available for >90%. The mean age predonation was 52.8 ± 11.5 years, 30 donors having pre-existent hypertension. The mean follow-up was 5.1 ± 0.9 years. Eight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
5
6
0
Order By: Relevance
“…Nevertheless, scores still remained higher than scores of the general population [34], and equaled baseline values after twelve months. These findings are in line with recent studies of Janki et al [41, 42], which support our findings that there are no negative short-term consequences for donors with regard to the physical domains of HRQOL.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, scores still remained higher than scores of the general population [34], and equaled baseline values after twelve months. These findings are in line with recent studies of Janki et al [41, 42], which support our findings that there are no negative short-term consequences for donors with regard to the physical domains of HRQOL.…”
Section: Discussionsupporting
confidence: 94%
“…Mjoen et al revealed women aged > 50 years with a BMI > 25 kg/m 2 as being at high risk for decreased renal function [7]. In a most recent study, GFR decreased about 33.6% and was longitudinally lower among men than women, without any association to HRQoL [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has mostly used generic HRQoL instruments that do not capture specific relevant donation-related domains [10,11]. The donor's perception on donation consequences for themselves, the recipient and their relationship before and after transplantation has mostly been described in retrospective or qualitative studies [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%